Discrepancy Between Emotion Regulation Assessment Using Self and Observative Reports at Taman Posyandu Anak Salih Karanganyar Paiton - Lailatul Fitriyah; Soviatul Widad; Fifi Sofiya; Laili Yetus Solehah; Qurratu A'yunina (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines the congruence between external observations (teachers/parents) and students' self-assessments of emotion regulation at Taman Posyandu Anak Salih Karanganyar Paiton. Emotion regulation is vital for adaptive emotional responses. Data are collected using the Emotion Regulation Checklist (ERC) for external observations and the Difficulties in Emotion Regulation Scale (DERS) for self-assessments. Findings reveal discrepancies between the two methods. The ERC shows most students exhibit adequate emotion regulation, particularly in adaptability (average score: 2.9), but struggle with emotional lability (2.1), characterized by instability and mood swings. Conversely, DERS indicates moderate emotion regulation difficulties (average score: 33.58), with primary challenges in impulse control (3.02) and goal-focused behavior under distress (2.55). Low, insignificant correlations between ERC and DERS suggest students' self-perceptions do not always align with external evaluations.The study highlights the need for a holistic approach, integrating internal and external perspectives on emotion regulation. It recommends collaborative interventions among teachers, parents, and students through Social-Emotional Learning (SEL) programs and regular evaluations to address students' emotional challenges effectively.